AN ETHNOGRAPHIC STUDY OF ENGLISH AND ARABIC MENDICANCY: A CRITICAL DISCOURSE ANALYSIS - Fojan, Jinan Abdulhasan; Abdulkareem, Ibtihal Mahdi (Veredas do Direito, 2026)
The current study investigates mendicancy or the act of begging from two interdisciplinary fields: critical discourse analysis and ethnography of communication . This study aims to fill a contextual gap by studying one social phenomenon from two different cultures with different social norms. It suggests that there are common linguistic strategies used by beggars in both English and Arabic -speaking communities . It also suggests that mendicancy reflects power structures , marginalization and social exclusion . The research also seeks to analyze and identify the diversity between cultures towards mendicancy. Data was collected from two States of America: New York and Florida, as well as two sides of Baghdad Alkarkh and Al-Rusafa. The analysis of the research is designed according to an analytical model that links two models: Fairclough’s three dimensional (1995) with some aspects of Hymes' SPEAKING model (1962) . New techniques and research tools were used, such as the Transkriptor application, interviews, and field notes. Critical discourse analysis was used to explore the discursive manifestations of ideology and the power of mendicancy whereas ethnography of communication reflects different perspectives of mendicants in receiving their messages and elicit empathy from passersby .The main conclusions that this study arrived at are as follows: what mendicants did not say is as important as what they said; they have the right to express their needs by using certain linguistic strategies , and what is surrounding mendicancy discourse represents a challenge in understanding how language works within different environments; and finally, despite the existing diversity between cultures, there is still a complex discourse that must shed light on and takes into consideration social norms that governed mendicancy discourse.